ANALISIS RETORIKA DAKWAH HABIB HUSEIN JA’FAR AL HADAR - Ifta, Muhammad Faiz Ridlolla (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2023)
The rhetoric of da'wah is also the skill of conveying the teachings of Islam verbally to provide the right understanding to Muslims, so that they can easily accept the call of Islamic da'wah. Podcast is a technology used to distribute, receive, and listen to content on demand that can be produced by professionals and amateurs. The problem in this study is how the rhetoric of Habib Husein Ja'far Al Hadar's da'wah through podcasts. The purpose of this research is to find out how Habib Husein Ja'far Al Hadar's preaching rhetoric through podcasts. This study uses a qualitative method with a type of library research, which is descriptive in nature. Then the techniques used are observation and documentation, and data analysis using content analysis. Keywords : Rhetoric of Da'wah; Habib Hussein Ja'far Al Hadar; Podcast;